The Effect of Joyful Learning Strategies on the results of learning to understand Quadratic Functions: The Effect of Joyful Learning Strategies - sugyarto (Journal of diversity in learning (JDIL), 2020)
This research is a Class Action Research (PTK), which aims to improve the mathematics learning results of grade IX students in quadratic function material by using the Joyful Learning Strategy. The subjects in this study were 28 students of grade IX-A SMPN 3 Ngimbang. Data collection techniques in this research include observation, interviews, tests, and documentation. The data obtained in this study have student learning results are taken from giving test questions at the end of the cycle, teacher's ability to manage to learn taken from observation sheets, and student activities taken from student observation sheets. The joyful learning strategy's implementation is carried out in 2 cycles consisting of the planning stage, implementation stage, observation stage, and reflection stage. The precycle research results showed that the average grade score obtained was 26.41%; after being given action in the first cycle using joyful learning, strategies experienced increased learning outcomes with a middle-grade score of 61.11% with students completing as many as 24 students or 85.71%. These results show an increase in student learning outcomes with the implementation of joyful learning strategies.